Accessing Intracellular Targets through Nanocarrier-Mediated Cytosolic Protein Delivery. (October 2020) - Goswami, Ritabrita; Jeon, Taewon; Nagaraj, Harini; Zhai, Shumei; Rotello, Vincent M.
Abstract : Protein-based therapeutics have unique therapeutic potential due to their specificity, potency, and low toxicity. The vast majority of intracellular applications of proteins require access to the cytosol. Direct entry to the cytosol is challenging due to the impermeability of the cell membrane to proteins. As a result, multiple strategies have focused on endocytic uptake of proteins. Endosomally entrapped cargo, however, can have very low escape efficiency, with protein degradation occurring in acidic endolysosomal compartments. In this review, we briefly discuss endosomal escape strategies and review the strategy of cell membrane fusion, a recent strategy for direct delivery of proteins into the cell cytoplasm . Highlights: Intracellular protein delivery is a powerful tool for development of protein-based therapeutics and is a challenging task due to cell membrane impermeability to large biomolecules and endosomal entrapment. Most delivery strategies rely on endosomal uptake of the carrier. Endosomally entrapped cargo generally exhibit low escape efficiency leading to eventual degradation. Numerous nanocarriers such as lipid, inorganic, and polymeric NPs have been developed to induce endosomal escape and deliver therapeutic proteins intracellularly. However, there remains considerable room for improvement in release efficiency. Development of nonendosomal uptake strategies including nanocarrier-mediated cell membrane fusion provides a promising alternative for delivering proteins directly to the cytosol. Improvements in protein delivery efficiency have enabled the translation of intracellular protein therapeutics towards the clinic.